Climate-Smart Healthcare : Low-Carbon and Resilience Strategies for the Health Sector - World Bank (World Bank, Washington, DC, 2017)
Climate change is damaging human health now and is projected to have a greater impact in the future. Low- and middle-income countries are seeing the worst effects as they are most vulnerable to climate shifts and least able to adapt given weak health systems and poor infrastructure. Low-carbon approach can provide effective, cheaper care while at the same time being climate smart. Low-carbon healthcare can advance institutional strategies toward low-carbon development and health-strengthening imperatives and inspire other development institutions and investors working in this space. Low-carbon healthcare provides an approach for designing, building, operating, and investing in health systems and facilities that generate minimal amounts of greenhouse gases. It puts health systems on a climate-smart development path, aligning health development and delivery with global climate goals. This approach saves money by reducing energy and resource costs. It can improve the quality of care in a diversity of settings. By prompting ministries of health to tackle climate change mitigation and foster low-carbon healthcare, the development community can help governments strengthen local capacity and support better community health.